Kualitas Pelayanan Publik Dinas Pendidikan Kebudayaan Kepemudaan dan Olahraga Kabupaten Semarang - Emilia, Setyani Hilda; Anissa Susiyanti (DOKTRINA: JOURNAL OF LAW, 2024)
This study aims to determine the standard of Service, workload, and quality of Public Services at the Department of Education, Culture, Youth, and Sports Semarang Regency. This study uses descriptive qualitative research methods based on a descriptive approach. The results showed Disdikbudpora Kab. Semarang has several service standards, namely legalized services, school transfer recommendation letter Services, Research recommendation services, diploma writing error certificate services, diploma replacement certificate services, new student admission services (PPDB), arts institution endorsement services, sports institution endorsement services, and Gor wujil rental services. Disdikbudpora Kab. Semarang has a large workload because the department holds 4 tasks at once in the form of 1) Education, 2) culture, 3) youth and 4) sports. In 2021 and 2022 Disdikbudpora Kab. Semarang has improved the quality of service to its community from good (82) to very good (92).